(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The major goal of this research is to use the spectral Petrov-Galerkin method (SPGM) to solve the first type of Volterra integral equations (VIEs). Three examples will be given to demonstrate how the suggested technique works, in comparison to the examples in [1] and [11], where the numerical and exact solutions are quite harmonic, effectively indicating the numerical answers. The absolute errors were determined to estimate the validity of the suggested method and to demonstrate that it was an effective and valid method.